A Comparative Study of Radon Levels in Federal Buildings and Residential Homes in Canada. Issue 3 (September 2019) - Whyte, Jeffrey; Falcomer, Renato; Chen, Jing
Abstract : Abstract: Shortly after revision of the Canadian radon guideline from 800 to 200 Bq m −3, Health Canada established the Federal Building Testing Program in 2007 to demonstrate federal leadership in raising awareness about radon risk and the need for testing. By the end of 2017, more than 7, 600 federal workplaces had been tested for radon. As is the case in all radon surveys, radon levels vary widely; federal building results ranged from below the detection limit to more than 2, 500 Bq m −3 in a few rooms of a few buildings. Weighted by the population of federal public servants across Canada, the average radon distribution in federal workplaces has a geometric mean of 22.0 Bq m −3 with a geometric standard deviation of 2.3. The population-weighted arithmetic mean is 34.3 Bq m −3, significantly lower than the population-weighted average radon concentration of 72.9 Bq m −3 in residential homes across Canada. On average, 2% of federal workplaces have radon concentrations above 200 Bq m −3, which is also significantly lower than the 7% of residential homes that tested above 200 Bq m −3 . This comparative study demonstrated clearly that radon education and awareness in Canada should focus more on residential testing and remediation actions to effectively reduce the burden of radon-induced lung cancer.